Firearm storage patterns in US homes with children. - Schuster, M A (2000)
OBJECTIVES: This study determined the prevalence and storage patterns of firearms in US homes with children. METHODS: We analyzed data from the 1994 National Health Interview Survey and Year 2000 objectives supplement. A multistage sample design was used to represent the civilian noninstitutionalized US population. RESULTS: Respondents from 35% of the homes with children younger than 18 years (representing more than 22 million children in more than 11 million homes) reported having at least 1 firearm. Among homes with children and firearms, 43% had at least 1 unlocked firearm (i.e., not in a locked place and not locked with a trigger lock or other locking mechanism). Overall, 9% kept firearms unlocked and loaded, and 4% kept them unlocked, unloaded, and stored with ammunition; thus, a total of 13% of the homes with children and firearms--1.4 million homes with 2.6 million children--stored firearms in a manner most accessible to children. In contrast, 39% of these families kept firearms locked, unloaded, and separate from ammunition. CONCLUSIONS: Many children live in homes with firearms that are stored in an accessible manner. Efforts to prevent children's access to firearms are needed.